The Depreciation of the Rupiah and the Increase in Tourist Arrivals: A PESTEL Analysis of Indonesia’s Tourism Competitiveness - Mahadiansar Mahadiansar; Agus Rio; Yudithia Yudithia; Ilham Sentosa (CV. Austronesia Akademika, 2026)
This study examines the relationship between the depreciation of the Indonesian rupiah and the increase in international tourist arrivals through a PESTEL analysis of Indonesia’s tourism competitiveness. The issue is important because currency depreciation may improve destination affordability for foreign tourists, yet its contribution to competitiveness depends on broader political, economic, social, technological, environmental, and legal conditions. Using a qualitative descriptive design, this article relies entirely on secondary data, including exchange rate information, tourism statistics, government documents, institutional reports, and scholarly literature. The analysis shows that rupiah depreciation can strengthen Indonesia’s price competitiveness by increasing foreign tourists’ purchasing power and making tourism services relatively cheaper. However, this advantage is conditional because tourism businesses may also face higher operational costs, especially when they depend on imported inputs, foreign-denominated expenses, and international digital platforms. The findings further indicate that tourist arrivals are shaped by digital visibility, online reviews, destination image, policy coordination, community readiness, environmental carrying capacity, and regulatory certainty. Therefore, rupiah depreciation should not be treated as an independent driver of tourism growth, but as a temporary opportunity that must be supported by integrated destination governance, sustainable management, digital promotion, and local economic participation. The study concludes that Indonesia’s tourism competitiveness will improve only if short-term affordability is transformed into long-term, inclusive, and sustainable destination value for future national tourism development.